2013
DOI: 10.1007/s00018-013-1457-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine functions of TIMP-1

Abstract: The tissue inhibitors of metalloproteinases (TIMPs) are well recognized for their role in extracellular matrix remodeling by controlling the activity of matrix metalloproteinases (MMPs). Independent of MMP inhibition, TIMPs act as signaling molecules with cytokine-like activities thereby influencing various biological processes including cell growth, apoptosis, differentiation, angiogenesis, and oncogenesis. Recent studies on TIMP-1's cytokine functions have identified complex regulatory networks involving a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
213
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(233 citation statements)
references
References 123 publications
10
213
0
4
Order By: Relevance
“…17 TIMP-1 may act as a signaling molecule to influence cell growth, cell differentiation, or miRNA-mediated post-transcriptional regulation. 43 In a study with adenovirus-mediated TIMP-1 overexpression in cardiac fibroblasts, the overexpression of TIMP-1 was associated with increased cell proliferation but not with changes in collagen content. 16 Our results showed that the concentration of TIMP-1 increased with an increasing concentration of aldosterone, and that this increase in TIMP-1 concentration was associated with a decrease in MMP-1 activity.…”
Section: Discussionmentioning
confidence: 97%
“…17 TIMP-1 may act as a signaling molecule to influence cell growth, cell differentiation, or miRNA-mediated post-transcriptional regulation. 43 In a study with adenovirus-mediated TIMP-1 overexpression in cardiac fibroblasts, the overexpression of TIMP-1 was associated with increased cell proliferation but not with changes in collagen content. 16 Our results showed that the concentration of TIMP-1 increased with an increasing concentration of aldosterone, and that this increase in TIMP-1 concentration was associated with a decrease in MMP-1 activity.…”
Section: Discussionmentioning
confidence: 97%
“…특히 MMP-9은 tumor necrosis factor-alpha (TNF-α), interleukin-6와 같은 내 독소 염증성 매개체 자극으로 발현이 증가하는 것이 특징이며 섬유아세포에서 collagen의 분해를 촉진시킨다 (Sanceau 등, 2002). MMPs의 활성을 조절하는 인자로 알려진 MMPs의 조직 억제인자(tissue inhibitors of MMPs, TIMPs)는 21-30 kDa의 분자량을 가지며 TIMP-1, TIMP-2, TIMP-3, TIMP-4 등 4종이 알려져 있으며 다양한 유형의 세포에 의해 발현된다 (Iwata 등, 1996;Ries 2014). TIMPs는 MMP와 비 공유적인 결합을 하여 MMP의 기능을 억제하는 것으로 알려져 있고, TIMP-1은 MMP-9과, TIMP-2는 MMP-2와 각각 결합하여 세포 간 기질의 파괴와 재형성 간의 균형을 조절하는 역할을 한다 (Johnson 등, 1994).…”
unclassified
“…TIMPs participate in the degradation of extracellular matrix, angiogenesis, apoptosis, differentiation, as well as in proliferation of normal and tumor cells (40). In this regard, patients with melanoma at Stages I-III in comparison with the control group had significantly higher median concentrations of serum TIMP-1, and this increase had an effect on disease-free survival and overall survival.…”
Section: Endogenous Enzyme Inhibitorsmentioning
confidence: 99%